Genetic variation at the MHC DRB1 locus is similar across Gunnison's prairie dog (Cynomys gunnisoni) colonies regardless of plague history - Cobble, Kacy R. (Ecol Evol, 2016)
Yersinia pestis was introduced to North America around 1900 and leads to nearly 100% mortality in prairie dog (Cynomys spp.) colonies during epizootic events, which suggests this pathogen may exert a strong selective force. We characterized genetic diversity at an MHC class II locus (DRB1) in Gunnison's prairie dog (C. gunnisoni) and quantified population genetic structure at the DRB1 versus 12 microsatellite loci in three large Arizona colonies. Two colonies, Seligman (SE) and Espee Ranch (ES), have experienced multiple plague‐related die‐offs in recent years, whereas plague has never been documented at Aubrey Valley (AV). We found fairly low allelic diversity at the DRB1 locus, with one allele (DRB1*01) at high frequency (0.67–0.87) in all colonies. Two other DRB1 alleles appear to be trans‐species polymorphisms shared with the black‐tailed prairie dog (C. ludovicianus), indicating that these alleles have been maintained across evolutionary time frames. Estimates of genetic differentiation were generally lower at the MHC locus (F (ST) = 0.033) than at microsatellite markers (F (ST) = 0.098). The reduced differentiation at DRB1 may indicate that selection has been important for shaping variation at MHC loci, regardless of the presence or absence of plague in recent decades. However, genetic drift has probably also influenced the DRB1 locus because its level of differentiation was not different from that of microsatellites in an F (ST) outlier analysis. We then compared specific MHC alleles to plague survivorship in 60 C. gunnisoni that had been experimentally infected with Y. pestis. We found that survival was greater in individuals that carried at least one copy of the most common allele (DRB1*01) compared to those that did not (60% vs. 20%). Although the sample sizes of these two groups were unbalanced, this result suggests the possibility that this MHC class II locus, or a nearby linked gene, could play a role in plague survival.